The Use of Landsat Image and Census Data for Modelling Population Density and Urban Density in Palembang, Indonesia - Muhammad Fajri Romdhoni (Journal of Architectural Research and Design Studies, 2020)
This research is to understand the condition of population Density concentration in the city of Palembang. According to the 2018 United nations booklet (United Nations, 2018), Palembang's city is dimmed to be one of the fastest-growing cities in Indonesia. Palembang has an annual growth rate between 2.4% to 6%, and according to the research, the exponential growth will impact its urban fabric conditions. The researcher's problem in urban growth is the limitation of datasets available from the government, and mostly the datasets are not tailored for urban designers need. The statistical datasets available are often linked to the administrative area called "kecamatan" without knowing the true population density in that particular area. This paper is using Landsat images and population density data, acquired respectively from Earth Explorer USGS and Balai Pusat Statistik to verify the morphological changes that has happened in Palembang between the year 2001, 2007, and 2016. The result output shows the LUDI / Land use dynamic Index and also verifying the density of each "kecamatan" as and administrative area in Palembang. The research output may contribute in the development of spatial research in urban design in Palembang. It could also help future research for urban development and population density verification in the city of Palembang.Keywords: Administrative area; Landsat images; Population density; Urban.